Kepastian Hukum Tenggang Waktu Pemanggilan dan Penetapan Sidang dalam Peradilan Perdata - Muhamad Rizki Firdaus; Grand Ace Jordan; Anggi Sri Haryati Simarmata (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
The implementation of civil justice in Indonesia is fundamentally guided by the principles of simplicity, speed, and low cost. However, in practice, the regulation concerning the time limits for summons and the determination of trial schedules remains inadequate, leading to legal uncertainty. This study aims to analyze the legal certainty of time limits in summons and trial scheduling within civil procedural law, as well as to examine its implications for the effectiveness of case resolution. This research employs a normative legal method with statutory and conceptual approaches, supported by a descriptive-analytical design. The findings indicate that existing regulations, particularly those derived from the Herzien Inlandsch Reglement (HIR) and Rechtsreglement voor de Buitengewesten (RBg), only provide minimum standards for summons but do not comprehensively regulate the timeframe for determining the first hearing or intervals between subsequent hearings. As a result, there is broad discretion in judicial practice, which leads to inconsistencies among courts, repeated trial delays, increased litigation costs, and reduced access to justice. Although recent reforms through electronic court systems have improved the mechanism of summons delivery, they have not sufficiently addressed the issue of time management in trial proceedings. This study concludes that the absence of clear and comprehensive regulations on trial timeframes weakens legal certainty and hinders the realization of efficient judicial processes. Therefore, strengthening normative regulations on trial scheduling is essential to support a more effective, predictable, and equitable civil justice system.